2022
DOI: 10.1016/s2666-5247(21)00280-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of the SARS-CoV-2 ARCoV mRNA vaccine in Chinese adults: a randomised, double-blind, placebo-controlled, phase 1 trial

Abstract: Background Safe and effective vaccines are urgently needed to end the COVID-19 pandemic caused by SARS-CoV-2 infection. We aimed to assess the preliminary safety, tolerability, and immunogenicity of an mRNA vaccine ARCoV, which encodes the SARS-CoV-2 spike protein receptor-binding domain (RBD). Methods This single centre, double-blind, randomised, placebo-controlled, dose-escalation, phase 1 trial of ARCoV was conducted at Shulan (Hangzhou) hospital in Hangzhou, Zhejian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…1a), it is interesting to assess the neutralizing activity of serum samples from vaccinees of ARCoV against the Omicron variant. To do so, a panel of serum samples (n = 11) from participants in the phase 1 clinical trial 10 were analyzed for their neutralizing Ab titers using VSV-based pseudovirus. All samples were collected on day 14 post two-dose immunization with 15 µg of ARCoV.…”
mentioning
confidence: 99%
“…1a), it is interesting to assess the neutralizing activity of serum samples from vaccinees of ARCoV against the Omicron variant. To do so, a panel of serum samples (n = 11) from participants in the phase 1 clinical trial 10 were analyzed for their neutralizing Ab titers using VSV-based pseudovirus. All samples were collected on day 14 post two-dose immunization with 15 µg of ARCoV.…”
mentioning
confidence: 99%
“…Collectively, our present study clearly demonstrated that a 3 rd dose of heterologous boosting with AWcorna was safe and potential protective against the circulating Delta and Omicron variants. Compared with phase 1 trial, the total IRs of local and systemic AEs for AWcorna booster showed significant improvement 10 , especially the IR of grade 3 fever reduced to 4% (Supplementary information, Table S4 ), which was comparable to the other two approved mRNA vaccines 11 . The phase 1 trial of AWcorna only included 20 adults aged 18-59 (15 μg group), while our present cohort enrolled 200 participants, including 10 subjects aged over 60.…”
Section: Discussionmentioning
confidence: 82%
“…Then, the literature was screened by the following criteria: (1) healthy participants older than 16 years; (2) a sample size of at least 100 participants; (3) randomized controlled design; and (4) the most recent study phase. A total of 33 studies met the inclusion criteria [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], and we extracted the vaccine platform, name, location, age, study phase, sample size, and safety data (especially the neurological AEs) from the included clinical trials (Table 2 ). Moreover, it must be noted that vaccine-unrelated AEs as specified in the articles have been excluded.…”
Section: Systemic and Neurological Aes Following Vaccinationsmentioning
confidence: 99%